2022
DOI: 10.3390/ijerph19063708
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about Pain Control in Patients after Abdominal Aortic Aneurysm Surgery—A Preliminary Study

Abstract: Introduction: Pain-control beliefs significantly influence the perception of disease and, therefore, may influence the treatment outcomes of surgical patients. The sense of control is related to the sense of agency and the ability to influence one’s own life and environment. This construct may be external or internal. The belief that pain control depends on internal or external factors can depend on many variables. This may be influenced by socio-demographic and clinical characteristics, as well as the source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Moderate to severe pain is common in spine surgery, and patients undergoing spine surgery often require analgesics, including opioids. 8,37 Parallel to the literature, half of the participants in our study received opioids in their standard analgesic therapy. The only study on pain beliefs and opioid consumption reported that the organic pain beliefs of patients who were administered opioids were significantly stronger.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate to severe pain is common in spine surgery, and patients undergoing spine surgery often require analgesics, including opioids. 8,37 Parallel to the literature, half of the participants in our study received opioids in their standard analgesic therapy. The only study on pain beliefs and opioid consumption reported that the organic pain beliefs of patients who were administered opioids were significantly stronger.…”
Section: Discussionmentioning
confidence: 99%